THE EFECTIVENESS OF USING AUTHENTIC READING MATERIALS TOWARD STUDENTS’ READING COMPREHENSION MASTERY - Diyah Dwi Agustina; Adelina Anum (Journal of English Development, 2021)
Abstract A difficult reading material has become one of the student problems in comprehending the text. The application of using Authentic Reading Materials is needed for students. This research aims to know the effectiveness of using Authentic Reading Materials towards the students reading comprehension mastery. This experimental research used quantitative method and queasy experimental design. The research conducted at the sixth grade of English Education Department of Nahdlatul Ulama Lampung University which has the population 8 classes. The sample used in this research is 20 students as experimental class and 20 students as control class. The researcher uses purposive sampling as technique sampling. Based on the result of T test formula, tratio is 4,61 and ttable is 2,44. It means that tcount > ttable. The result of this research indicates that using Authentic Reading Materials is effective towards the students reading comprehension mastery at the sixth grade of English Education Department of Nahdlatul Ulama Lampung University